REAL TOPONYMS AS EXTRATEXTUAL SIGNS OF VERTICAL CONTEXT - Слободяк, Світлана (SWorldJournal, 2024)
The article deals with the functioning of real toponyms in literary texts. Their primary function is to localize the place. The use of toponyms in the localizing function helps the author to outline the geographical contours of the depicted artistic space